Comparison of the effect of gonadotropin-releasing hormone agonist dosage in girls with central precocious puberty - Shinyoung Jang; Su Jin Kim; Myeongseob Lee; Hae In Lee; Ahreum Kwon; Junghwan Suh; Kyungchul Song; Hyun Wook Chae; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2023)
Purpose There are no definite guidelines on the optimal dosage of gonadotropin-releasing hormone (GnRH) agonist for treatment of central precocious puberty (CPP). We compared growth outcomes of GnRH agonist at different dosages in girls with idiopathic CPP to assess the optimal dosage. Methods This retrospective study included 86 girls with idiopathic CPP who had been treated with GnRH agonist for at least one year and had attained their final adult height. Leuprolide was given as fixed dosage (3.75 mg every 4 weeks in body weight >20 kg, n=72) or weight-based dosage (60-85 μg/kg every 4 weeks, n=14). We compared suppression of advanced puberty and treatment response between the 2 groups. Results Peak estradiol and luteinizing hormone and bone age (BA)/chronological age after injection of GnRH agonist were effectively suppressed in both groups. In both groups, the height standard deviation score (SDS) for BA increased after treatment. Final adult height (FAH) (fixed dosage group,160.8±4.1 cm and weight-based dosage group, 161.2±4.4 cm) was significantly higher than the initial predicted adult height (PAH) (155.5±3.3 and 156.1±3.6 cm, respectively) (both P<0.001) and similar to midparental height (159.8±3.3 and 160.6±3.7 cm, respectively). There were no differences in gain in height SDS for BA and gain in height (FAH-PAH at the start) between the 2 groups. Conclusions There were no differences in treatment outcome between fixed dosage (3.75 mg/4 wk) and weight-based dosage (60-85 μg/kg/4wk) of GnRH agonist. Therefore, a fixed dosage of GnRH agonist can be used more conveniently for CPP treatment without growth oversuppression.